Koneman's COLOR ATLAS AND TEXTBOOK OF Diagnostic Microbiology - Procop, Gary W.; Church, Deirdre L.; Hall, Geraldine S.; Janda, William M.; Koneman, Elmer W.; Schreckenberger, Paul C.; Woods, Gail L. (Wolters Kluwer Health, 2017)
"The founding objective of Koneman's Color Atlas and Textbook of Diagnostic Microbiology is to provide a clear exposition of procedures routinely employed in the laboratory identification of microbial agents causing infectious diseases"--